1993
DOI: 10.1111/j.1365-2362.1993.tb00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Very long chain n‐3 and n‐6 polyunsaturated fatty acids inhibit proliferation of human T‐lymphocytes in vitro

Abstract: The effect of marine n-3 polyunsaturated fatty acids on proliferation of human T-cells in vitro was compared to other polyunsaturated, monounsaturated and saturated fatty acids. Monoenes and saturated fatty acids had little effect on T-cell proliferation. Eicosapentaenoic acid and docosahexaenoic acid exerted a strong dose-dependent inhibitory effect on proliferation of mitogen- or antigen-stimulated T-cells, similar to that observed for arachidonic acid. Sixty microM of albumin-bound eicosapentaenoic acid or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 41 publications
7
70
2
Order By: Relevance
“…11,15 However, in two very similar reports, the addition of antioxidants together with PUFA had no reversible effect. 14,16 As none of these studies investigated if the reduced cell multiplication with PUFA was caused by apoptosis or necrosis, the discrepancies in these reports may be explained by our present findings. The conversion of AA and EPA to their respective eicosanoids has been proposed as an alternative mechanism for modulation of cancer cell multiplication.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…11,15 However, in two very similar reports, the addition of antioxidants together with PUFA had no reversible effect. 14,16 As none of these studies investigated if the reduced cell multiplication with PUFA was caused by apoptosis or necrosis, the discrepancies in these reports may be explained by our present findings. The conversion of AA and EPA to their respective eicosanoids has been proposed as an alternative mechanism for modulation of cancer cell multiplication.…”
Section: Discussionmentioning
confidence: 55%
“…12,13 Moreover, n-3 fatty acids and some other polyunsaturated fatty acids (PUFA) may decrease DNA synthesis and viability of cultured human lymphocytes. [14][15][16] It is not known whether effects of n-3 fatty acids on tumor size, metastasis, cell number or DNA synthesis are due to alterations in cell proliferation, cell differentiation or induction of the two main forms of cell death, necrosis and apoptosis. In a previous study on a promyelocytic leukemia cell line (HL-60), a reduced cell multiplication rate and DNA synthesis was observed after incubation with PUFA, and this was ascribed to effects on cell differentiation and cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that diets containing oils or fatty acids added to the culture medium have strong effects on lymphocyte functions, in both animals and humans [1][2][3][4]. Polyunsaturated fatty acids (PUFA) such as (n-3) PUFA suppressed mitogen-stimulated proliferation of lymphocytes isolated from lymph nodes [ 1 ] and spleen of rats [ 5 ] , as well as from spleen of mice [ 5 ] and peripheral blood mononuclear cells from humans [4].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies agree that saturated fatty acids cause less inhibition than unsaturated fatty acids (Mertin & Hughes, 1975;Calder et al 1991Calder & Newsholme, 1992a,b;Soyland et al 1993;Rotondo et al 1994); there have been a number of reports of lack of inhibition by lauric and myristic acids (Weyman et al 1975Tsang et af. 1977;Calder et al 1991Calder & Newsholme, 1992a,b;Soyland et al 1993) and there appears to be general agreement that stearic acid is the most potent inhibitor of lymphocyte proliferation amongst the saturated fatty acids, causing a degree of inhibition similar to that of oleic acid (Calder et al 1991Calder & Newsholme, 1992a,b;Soyland et al 1993). Thus, amongst the saturated fatty acids the order of potencies appears to be:…”
Section: Fatty Acids a N D Lymphocyte Functions In Vztro Lymphocyte Pmentioning
confidence: 99%
“…1975Weyman et af. , 1977Tsang et al 1977;Buttke, 1984;Virella et al 1989;Calder et al 1990aCalder et al , 1991Calder & Newsholme, 1992a,b;Kumar et al 1992;Soyland et al 1993;Rotondo et al 1994). These studies show that oleic, linoleic, a-linolenic, y-linolenic, dihomo-y-linolenic, arachidonic, eicosapentaenoic and docosahexaenoic acids inhibit concanavalin A (Con A)-and/or phytohaemagglutinin (PHA)-stimulated proliferation of lymphocytes isolated from rodent lymphoid tissues (lymph nodes, spleen, thymus) and from human peripheral blood and have been reviewed in detail elsewhere (Yaqoob & Calder, 1993;.…”
Section: Fatty Acids a N D Lymphocyte Functions In Vztro Lymphocyte Pmentioning
confidence: 99%